To talk about mathematics (in three languages) in order to understand mathematics (Journal of Parents and Teachers, 2012)
In this article, the author tries to offer a new image of the process of learning of students doing maths. She also talks about an integrated proyect implemented in La Escuela Vila Olímpica as an example.
Keywords: Development; learning process; mathematics